Could, would, should: Theory of mind and deontic reasoning in Tongan children. Issue 5 (26th May 2022) - Taumoepeau, Mele; Kata, 'Ungatea Fonua; Veikune, 'Ana Heti; Lotulelei, Susana; Vea, Peseti Tupou'ila; Fonua, 'Ilaisaane
Abstract: This study examined the developmental profiles of children's social reasoning about individual agentive and deontic concerns. Tongan children ( N = 140, 47.9% male), aged 4–8 years, were given a set of mentalistic (standard theory‐of‐mind) and deontic reasoning tasks. On average, children found diverse desires, knowledge access, hidden emotion, and belief emotion easier than the false‐belief and diverse belief tasks. Tongan children were sensitive to social norms governing behavior, and this information was recruited for predicting behavior in a false‐belief task when embedded in a socially normative context. We discuss the potential for cultural mandates to shape children's social understanding and the impact of culture on our theoretical framing of children's development.